The making of Boeing 777: a case study in concurrent engineering. (4th October 2004) - Sharma, K.J.; Bowonder, B.
This is a case study on the concurrent engineering experience of Boeing 777. A new generation of aircraft was designed, developed and inducted in a record time. A variety of new technological and organisational enablers have been used to reduce costs and cycle time: horizontal coordination, clever and innovative use of existing and new designs and technologies, digital product definition, systems integration, and working together teams that included customer airlines and suppliers. Top management provided the necessary support.